2004
DOI: 10.1108/01425450410550464
|View full text |Cite
|
Sign up to set email alerts
|

Why do employees, particularly women, reject occupational pension schemes?

Abstract: An integral part of government policy is to encourage employees to make financial provision for retirement. This paper asks why eligible employees, particularly women, do not join their company schemes. This two‐stage study uses face to face interviews followed by a survey of 532 employees who have chosen not to become members of their company schemes. Findings highlight personal pension ownership and a requirement for flexibility and pension portability as the key reasons for non‐membership. The dominant reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Divorced men and women forgo the possibility of a survivor's pension, even if this was an expectation while married (Ginn, 2003). This is particularly problematic given that Gough (2004) found women's reasons for not joining occupational pension schemes included the expectation that their partner would provide for them in retirement (26 per cent of female respondents compared with 1 per cent of males). Therefore, there is an increasing recognition of the need for women to have their own independent pension in retirement (Price, 2007b).…”
Section: Gender and Occupational Pensionsmentioning
confidence: 89%
“…Divorced men and women forgo the possibility of a survivor's pension, even if this was an expectation while married (Ginn, 2003). This is particularly problematic given that Gough (2004) found women's reasons for not joining occupational pension schemes included the expectation that their partner would provide for them in retirement (26 per cent of female respondents compared with 1 per cent of males). Therefore, there is an increasing recognition of the need for women to have their own independent pension in retirement (Price, 2007b).…”
Section: Gender and Occupational Pensionsmentioning
confidence: 89%
“…Sefton et al (2008) indicate that women with higher pension incomes in older age are those who never married or who married later and never had children. Gough (2004) found that 26% of female employees said they had not joined occupational pension schemes because they expected their partner to provide for them in retirement. Increasing levels of divorce also affect pensions despite legislation allowing pension-sharing on divorce.…”
Section: Women Employment and Private Pensionsmentioning
confidence: 98%
“…Women's careers are more often characterised by movement between jobs and in and out of employment (Sefton et al, 2008). DB schemes typically operate with a one 60th principle for each year of service up to a maximum of 40 years, with a maximum income of two thirds of final salary in retirement (Gough, 2004). The best year of pensionable earnings in the last three years before leaving service usually represents the final pensionable earning.…”
Section: The History Of Private Pensionsmentioning
confidence: 99%
“…Gallhofer and Haslam (1997) identify repressed groups such as women, ethnic minorities, indigenous peoples, colonised peoples, the poor, the exploited, the disabled, children and the aged, whose needs an enabling accounting should recognise. Pension provision in the UK is unevenly distributed among the population with women (Ginn, 2001;Gough, 2004), poorly-paid workers, employees in small firms and ethnic minorities having the poorest levels of provision (Pensions Commission, 2004). In both the UK (Emmerson, 2003) and the USA (McCarthy and Neuberger, 2003), a tendency has been noted towards considerably better pension provision for the higher paid.…”
Section: The Pensions Crisis In the Ukmentioning
confidence: 99%